Monuments man : the mission to save Vermeers, Rembrandts, Da Vincis, and more from the Nazis' grasp - Rorimer, James J. (Rizzoli Electa, 2022)
A classic now back in print and enriched with new imagery, James J. Rorimer's riveting first-hand account takes readers on a treasure hunt as he follows the Allied troops across France and Germany to save Nazi-stolen masterpieces of art. James J. Rorimer, former director of the Metropolitan Museum of Art, became a leading figure in the art recovery unit known as the Monuments Men, an elite group imbedded in the US Army, who risked their lives during World War II to save Europe's greatest artworks from Hitler's grasp. In the film Monuments Men, Matt Damon's character is based on Rorimer as he embarks on the world's most dangerous real-life hunt for stolen artworks with the goal of locating, seizing, and returning the works to their original holders, including museums and private collectors. This new edition of a book first published in 1950 includes the original illustrations from the first edition plus a wealth of new imagery and ephemera uncovered during extensive research, including WWII photo-graphs, many taken by Rorimer himself, that are accompanied by gorgeous reproductions of many of the Old Masters Rorimer helped save by artists such as Rembrandt, Leonardo da Vinci, Bruegel, Vermeer, Goya, Velazquez, and van Eyck. Maps created specially for this volume, and other facts about WWII history and geography, add new dimension to a remarkable story of courage, perseverance, and ultimately, triumph